2022
DOI: 10.1136/bmjdrc-2021-002329
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in cardiometabolic risk profiles and gestational diabetes mellitus by nativity and acculturation: findings from 2016–2017 National Health Interview Survey

Abstract: IntroductionGestational diabetes mellitus (GDM) is a common complication of pregnancy with implications for cardiovascular health. Among reproductive-aged women, less is known about nativity-related disparities in cardiometabolic risk profiles and GDM history. We examined how cardiometabolic risk profiles and GDM history differed by nativity and explored associations between acculturation, cardiometabolic risk profiles and GDM history.Research design and methodsWe analyzed cross-sectional data from the 2016–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
2
5
0
Order By: Relevance
“…A major limitation is that self-reported physician-diagnosed GDM may under or overestimate the true prevalence of diagnosed GDM. However, the sensitivity and specificity of self-reported GDM have been reported in previous studies ( 16 ), and the self-reported GDM in NHIS has been widely used in other studies ( 45 , 46 ). Another potential limitation of this study is that information was limited on which criteria were used for the diagnosis of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…A major limitation is that self-reported physician-diagnosed GDM may under or overestimate the true prevalence of diagnosed GDM. However, the sensitivity and specificity of self-reported GDM have been reported in previous studies ( 16 ), and the self-reported GDM in NHIS has been widely used in other studies ( 45 , 46 ). Another potential limitation of this study is that information was limited on which criteria were used for the diagnosis of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Data from a cross-sectional US national survey found that foreign-born women with longer duration of US residence (≥10 years) had a greater odds of GDM history than US born women, suggesting that foreign-born women may acculturate and develop unhealthy behaviors that increase the risk of GDM. 23 In our study of HCHS/SOL participants, women who immigrated at age ≥30 years had a lower prevalence of GDM compared with those who immigrated as children (≤18 years); this may reflect underdiagnosis of GDM in a foreign country or underdiagnosis in earlier time periods before the importance of GDM on fetal and maternal health were established; it may also reflect acculturation in women who immigrated at a younger age. 24 We also found that the prevalence of self-reported GDM was higher for women with health insurance, which may reflect proper prenatal care and awareness, resulting in a lower likelihood that GDM goes undiagnosed.…”
Section: Discussionmentioning
confidence: 73%
“…While previous studies in the USA and Europe have found that foreign-born women have a higher prevalence of GDM,20–22 we found that the prevalence of self-reported GDM was similar for women born in the USA and women who immigrated and have lived in the USA for >15 years in our analysis of HCHS/SOL participants. Data from a cross-sectional US national survey found that foreign-born women with longer duration of US residence (≥10 years) had a greater odds of GDM history than US born women, suggesting that foreign-born women may acculturate and develop unhealthy behaviors that increase the risk of GDM 23. In our study of HCHS/SOL participants, women who immigrated at age ≥30 years had a lower prevalence of GDM compared with those who immigrated as children (≤18 years); this may reflect underdiagnosis of GDM in a foreign country or underdiagnosis in earlier time periods before the importance of GDM on fetal and maternal health were established; it may also reflect acculturation in women who immigrated at a younger age 24.…”
Section: Discussionmentioning
confidence: 99%
“…55 Recent evidence shows that acculturation, mostly capturing immigrants' birthplace and the duration of their stay in the host country, is associated with their health-related behaviors and health outcomes. 56,57 Chinese immigrants' acculturation influences chronic condition management in a complex way, which is shaped by various factors, such as their cultural background, their goals for acculturation, and the pressure they feel to assimilate. 58 The difference in their behavior indicates how Chinese immigrants understand the difference between cultural and societal norms and the strategies they took to manage this challenge.…”
Section: Discussionmentioning
confidence: 99%